Intangibles as innovative drivers for competitive businesses - Lopes, I. T.; Ferreira, C. F. P. (International Journal of Business Innovation and Research, 2021)
This paper aims to identify the impact of intangible resources as drivers of firms’ performance and profitability, in the major technological firms in the world. Using information from the major technological firms for a four years economic period, a set of intellectual capital proxies were identified and regressed against the major performance and profitability indicators. The regression model embodies a set of knowledge-based resources intangible (e.g. goodwill, licenses and patents, software and R&D, and advertising expenses) and human capital proxies, aiming to identify potential disaggregated effects of intangibles those key performance indicators. Broadly, results suggest the existence of effective isolated effect for some variables, in particular for intangibles recognized in the financial reporting. Furthermore, this research also suggests that the capitalization of intangible resources can be associated with region and corresponding accounting standards used in the preparation of the financial reporting.